E-Goat Doctor: An Expert System for the Diagnosis of Common Goat Diseases (International Journal of Engineering and Computer Science, 2024)
The E-Goat Doctor is an expert system designed to diagnose common goat diseases, particularly in rural areas where access to veterinary services is limited. Utilizing a rule-based algorithm, the system analyzes symptoms provided by users and matches them with known diseases, offering accurate and timely diagnoses. The development of the E-Goat Doctor involved series of consultations with domain experts, ensuring a comprehensive knowledge base that addresses prevalent goat health issues in Northern Mindanao, Philippines, such as mastitis, foot rot, pneumonia, worm infestations, Enterotoxemia, and Calcium Deficiency. During testing, the system demonstrated high accuracy in diagnosing diseases, making it a valuable tool for goat farmers. The E-Goat Doctor not only improves the efficiency of disease management but also contributes to the overall health and productivity of goat herds. This expert system is positioned to be a significant asset in supporting sustainable goat farming practices, especially in regions with limited veterinary support.